Mutagenesis on cyanobacteria for high CO2 uptake: a review - Shari, Ummi S. Halmi; Azmi, Azlin Suhaida; Amid, Azura; Ahmad Raus, Raha; Jimat, Dzun Noraini (Journal of Pure and Applied Microbiology, 2014)
Recently, mutagenesis on cyanobacteria has been performed to enhance carbon dioxide (CO2) bio-mitigation. The physical and chemical mutagens have been introduced on cyanobacteria to induce genetic mutation. Physical mutagen includes electromagnetic radiation, such as gamma rays, x-rays, and ultraviolet (UV) light, while the chemical mutagen includes are ethyl methanesulphonate (EMS), and N-methyl-N’-nitro-N-nitrosoguanidine (MNNG). Different types of mutagen, concentration, incubation period and temperature affect the rate of mutagenesis. As a result, various kinds of observation were produced. Thus, this review aims at providing an updated account of the research progress in mutagenesis on cyanobacteria and its application in CO2 mitigation enhancement.